Power, satisfaction, and relationship commitment in Chinese store-tenant relationship and their impact on performance - Ramaseshan, Balasubramanian; Yip, L.; Pae, J. (New York University, Elsevier Inc., 2006)
Managing the distribution channel is a key concern to firms operating in the world''s largest developing economy. This study examines channel exchange relationships in China using data on department stores’ relationship with their tenants. The power–satisfaction–commitment–performance framework was used as a basis for the study. Department stores’ contingent use of coercive power was found to have little or no effect on their tenants’ economic and social satisfaction, which suggests that coercive power is perceived as ‘legitimate’ by small and medium-sized retailers in China. Tenants’ behavior towards power also reflects a subtle difference in channel member behavior, which reflects the differences between China''s collectivistic culture and the individualistic culture in many Western countries. This study adds to the existing knowledge on channel behavior in Chinese cultural setting. In addition, it tests the degree of cross-cultural generalization of established channel constructs. It also provides managerial insights on channel relationship management in China's market.